The magic school bus in the time of the dinosaurs - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1994)
When Ms. Frizzle takes her class to a dinosaur dig to look for Maiasaura nests, the Magic School Bus turns into a time machine and transports them back into prehistoric times--when dinosaurs roamed the Earth.
Wilson's Children
Elem. School Library Collection
School Library Journal
4.0
K-3
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Time travel; Space and time; Dinosaurs; Space and time; Field trips